2016
DOI: 10.1111/dom.12605
|View full text |Cite
|
Sign up to set email alerts
|

Use of incretin agents and risk of pancreatic cancer: a population‐based cohort study

Abstract: We found that incretin use was not associated with pancreatic cancer after adjustment for the severity of the underlying Type 2 Diabetes Mellitus (T2DM). The elevated risk of pancreatic cancer in those recently initiating incretin agents is likely to be caused by protopathic bias or other types of unknown distortion. The presence of considerable confounding by disease severity and the lack of a duration-of-use relationship do not support a causal explanation for the association between incretin agents and panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(88 citation statements)
references
References 47 publications
4
81
1
2
Order By: Relevance
“…[12][13][14][15][16][17] Overall, most of these studies did not report statistically significant associations. 12-15 17 One study reported an overall increased risk with sitagliptin (hazard ratio 1.40, 95% confidence interval 1.13 to 1.75), but with no clear dose-response relation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[12][13][14][15][16][17] Overall, most of these studies did not report statistically significant associations. 12-15 17 One study reported an overall increased risk with sitagliptin (hazard ratio 1.40, 95% confidence interval 1.13 to 1.75), but with no clear dose-response relation.…”
Section: Discussionmentioning
confidence: 94%
“…[12][13][14][15][16][17] These studies have, however, provided conflicting results and several had methodological shortcomings. 18 Given this controversy, regulatory agencies have called for additional studies of this potential association.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of RCTs and various large noninterventional studies did not show an increased risk of pancreatic cancer in association with DPP‐4 inhibitors.…”
Section: Discussionmentioning
confidence: 90%
“…The United Kingdom (UK) Clinical Practice Research Datalink (CPRD) is one of the world's largest primary care databases and is frequently used for post‐authorisation safety studies, pharmaco‐epidemiology, and disease epidemiology . Examples include the evaluation of side effects of dopamine agonists or diabetes drugs, and the epidemiology of fractures…”
Section: Introductionmentioning
confidence: 99%